In Vitro Study of the Biological and Physical Properties of Dual-Cure Resin-Modified Calcium Silicate-Based Cement - Minjung Kim; Sung-Hoon Lee; Dong-Hoon Shin (MDPI AG, 2023)
Background: The aim of the present study was to compare the biological and mechanical properties of a novel dual-cure, resin-modified calcium silicate material, Theracal PT® (TP), with those of Theracal LC® (TL) and BiodentineTM (BD). Methods: The cell counting kit-8 was used on human dental pulp cells to test cell the viability of the three materials. Antibacterial activity of TP, TL, and BD against Enterococcus faecalis was investigated under anaerobic conditions. The ability of the materials to support odontogenic differentiation was studied by examining the relative gene expression of osteocalcin (OCN), osteopontin (OPN), and Collagen I (ColI) using real-time polymerase chain reaction. For mechanical property tests, microhardness was evaluated using the Vickers microhardness (VHN) test, and the bond strength to the resin was evaluated using a shear bond test machine. Results: There was no significant difference in cell viability between TL and TP after 48 h, and BD showed the highest cell viability, while TP showed the highest antibacterial effect. At the 12-h time point, there was no significant difference in ColI and OCN expression between BD and TP, but TP showed a higher expression of OPN than BD. However, at the 48-h time point, ColI and OCN showed higher levels of expression for BD than for TP and TL. At the same time point, only OPN had a higher diffusion for TP than for BD. TP demonstrated a VHN of approximately 30-35. This value was higher than that of TL and lower than that of BD. In contrast to VHN, the shear bond strength to resin was significantly higher for TL and TP than for BD. Conclusion: TP showed lower biocompatibility than BD but higher OPN expression and antibacterial effects than BD and TL. TP showed higher shear bond strength than BD and higher VHN than TL and BD at the 24-h time point.